Happy Bethday! - Knife; Packer (Knife. Badly drawn Beth, 2016)
So I'm being chased through the park by a pack of angry zombies, I've got cake mix on my face and MY MOST EMBARRASSING PHOTO EVER IS IN THE SCHOOL MAGAZINE! Beth Orsen is back for her third hilarious adventure.